(untitled) (Global Journal of Management and Business Research, 2019)
This paper aims to examine the effect of Activity Based Costing (ABC) system on corporate pricing decisions of the Jordanian industrial shareholding companies. Specifically, this paper aims at examining the effect of ABC system on corporate pricing decision. These decisions include: (i) setting the initial price, (ii)determining discounts, (iii)setting the final price and (ix) decision on competitive pricing analysis. Drawing from quantitative research methodology, a questionnaire was developed as the main tool for data collection, which included a sample of (352) employees in the Jordanian industrial shareholding companies. Using the linear regression model, we model the relationship between ABC system and the sub-variables of pricing decisions via the multiple linear estimations. The results from this model refer that there was significant (α ≤ 0.05) effect of ABC system on the pricing decisions of the Jordanian industrial companies, with a high degree of statistical significance of the variable of raising employee awareness on the importance of ABC on all independent variables of corporate pricing decisions.